WATER QUALITY STUDY TO BE TRANSFERRED INTO THE LIMA CITY FOR HUMAN CONSUMPTION - Méndez Q., Leonor (2001)
The study of water quality was carried out in 15 sources of the project «Final Study Diversion Pomacocha River Blanco (Marca II)» talking as reference the class II (water to be treated for domestic supply) and class VI (waters for aquatic fauna preservatlon and recreational or comercial fishing) of the Peruvian General Law of Waters with the twe following objectives: to determine if the water is apt for human consumption and to investigate the impact that would have the water diversion on the flora and fauna of the water bodies in all the traveled through.